Effects of the Layered Distribution Pattern on the Gas Flow Resistance through the Bed with the Multisize Irregular Particle for the Waste Heat Recovery - Sizong Zhang (International Journal of Photoenergy)
The application of the sinter vertical cooling technology in the iron and steel industry is conducive to the realization of the double carbon in China. To reduce the energy consumption and improve the economy of the new process, the gas flow resistance in the sinter bed under the layered distribution pattern was experimentally studied. The gas flow resistance of most of the layered distribution modes is lower than that of the random distribution mode. Among all layered arrangement modes, the layered mode with the particle size increasing from the bottom-up has the lowest resistance, followed by the layered mode with the particle size decreasing from the bottom-up. These two modes ensure the feasibility of the application of the layered distribution pattern in the continuous production of the moving bed. Besides, increasing the number of layers benefits the reduction of the gas flow resistance, which has a more significant effect on the layered mode with the particle size increasing from the bottom-up. For the sinter mixture with the equivalent particle diameter of 11.45 mm, the gas resistance of the modes with the particle size increasing and decreasing from the bottom-up decreases by 11.71% and 8.26% with the layer number increasing from three to five, respectively. Also, the effect of the layered distribution pattern on the gas flow resistance progressively weakens with increasing the equivalent particle diameter. For the five-layer distribution mode with the particle size increasing from the bottom-up, the gas resistance decreases by 2.72% with the equivalent particle diameter increasing from 11.45 mm to 15.45 mm, while that decreases by 4.61% with the equivalent particle diameter increasing from 15.45 mm to 19.45 mm. What's more, the change of the equivalent particle diameter has a more significant influence on the layered mode with the particle size decreasing from the bottom-up. With the equivalent particle diameter increasing from 15.45 mm to 19.45 mm under the five-layer distribution pattern, the gas resistance of the layered mode with the particle size increasing from the bottom-up reduces by 4.61%, while that of the mode with the particle size decreasing from the bottom-up reduces by 7.38%.